2015
DOI: 10.1186/s13089-015-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured splenic artery aneurysm detected by emergency ultrasound—a case report

Abstract: Splenic artery aneurysm is a rare but a potentially fatal condition. It is usually asymptomatic until it ruptures. Here, we present a case of ruptured splenic artery aneurysm in a 59-year-old gentleman presenting with epigastric pain and hypovolemic shock. The diagnosis was made by emergency ultrasound and CT scan, and he was managed by laparotomy and excision of the splenic artery aneurysm. Priorities in patient management lie in rapid resuscitation, diagnostic imaging, surgical consultation, and subsequent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The management of SAPAs and true splenic artery aneurysms has long been discussed under the same headings in most studies, although etiological factors, histopathologic features, prevalence as well as gender predominance differ (1,2,8). There is no debate on the point that a rapidly enlarging or ruptured aneurysm requires treatment, whether true or false (8,9). That said, debates on the management of asymptomatic, silent aneurysms are ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management of SAPAs and true splenic artery aneurysms has long been discussed under the same headings in most studies, although etiological factors, histopathologic features, prevalence as well as gender predominance differ (1,2,8). There is no debate on the point that a rapidly enlarging or ruptured aneurysm requires treatment, whether true or false (8,9). That said, debates on the management of asymptomatic, silent aneurysms are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors on this controversial topic have suggested that the mechanism behind the formation of the aneurysm is not a determining factor in the decision making process (9). Albeit less common, some such aneurysms are false, and their natural history may not be well-delineated, leading a significant number of authors to recommend the repair of all SAPAs, regardless of size and symptoms (1,3,8,10). We strongly advocate this view, having witnessed the devastating rupture of a SAPA that was overlook due to its small size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper abdominal pain is the most commonly reported symptom for ruptured SAAs [5, 6]. The clinical presentation of unruptured SAA is largely nonspecific and variable [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…Splenic artery aneurysm (SAA) is defined as an abnormal dilatation of splenic artery more than 1 cm in diameter [ 1 ]. It was first reported in 1770 by Beaussier and was described in a living person by Winkler in 1903 [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. SAA is an uncommon disease in the general population with incidence ranging from 0.09% in autopsy studies and 0.78% in arteriography studies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%